A DLP Module Design Based on Plug-in for MS Word - Hussein Al-sanabani; Murat İskefiyeli (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Inadvertent Data leakage by insiders is considered a serious problem for many organizations. Organizations are increasingly implementing Data Leakage/Loss Prevention solutions also know as (DLP), to protect the confidentiality of their data. Currently, DLP solutions have difficulties to identify confidential data as well as lack the ability to allow users to distinguish confidential from non-confidential data. Moreover, they are limited to work outside organizations. In order to solve this problem, it is important to introduce a DLP-Plugins model where the data owners can identify the privacy of the files during their entire lifecycle (creating, editing, etc.) by classifying them. This model uses security measures such as data encryption and access control to prevent accidental leakage of the classified files by the insiders. The proposed model guarantees that the right user will have access to the correct files according to their security access privilege inside or outside the organization. By always keeping classified files encrypted this will protect them all the time and everywhere. The DLP-Plugins model guarantees the usability for the users, all that will be required is to simply open and close the file as they do normally. As an example of the DLP-Plugins model, we have built a DLP-Plugin for Microsoft Word.